Composed for Solo Guitar or String Orchestra? The Fluid Incarnations and Pedagogical Opportunities of Wallace Stevens’s The Man with the Blue Guitar - Bart Eeckhout (Transatlantica)
This article elaborates the critical, editorial, and pedagogical challenges and opportunities raised by Wallace Stevens’s The Man with the Blue Guitar (both the book and the title poem). It ranges from a consideration of the title poem’s unpublished autograph and the preliminary appearance of a selection of cantos in Twentieth Century Verse and Poetry to the book published by Knopf in 1937, its subsequent repackaging in 1952, and the different ways in which especially the title poem has been integrated in selected, collected, and artistically augmented volumes for the English-speaking market, as well as in translation. Thus, a text-genetic narrative and publication history of continuous material transformations emerges that squares well with the aesthetics propagated and enacted by Stevens’s open series of variations on a theme.